Can Artificial Intelligence (AI) Become an Active Assistant to the Finance, Audit, and Accounting Functions? A Credit Control Data Analysis Approach - Bulau, Carmen Mihaela; Mustatea, Aura Oana; Matei (Pana), Mirela (Acta Universitatis Danubius. Œconomica, 2024)
This paper investigates the transformative role of the financial accountant/analyst and of Artificial Intelligence (AI) integration as a virtual assistant to the finance and accounting function of an organization, facilitating accurate financial analysis, interpretation, and presentation of key indicators while optimizing time efficiency. In today's fast-paced business environment, financial managers are tasked with navigating complex financial landscapes and providing timely insights to support strategic decision-making. Examining the challenges faced in performing financial analysis and interpretation while increasing data volumes and complexity, this research discusses how AI algorithms enable finance managers to automate data collection, analysis, and reporting tasks, thereby freeing up valuable time for strategic planning and decision-making. This research has been conducted by a financial specialist with more than 10 years of experience in the finance and accounting area interrogating a GenAI bot (ChatGPT bot – Finance Wizard), based on the given two years balance sheet and profit and loss financial statements data available for testing. The scope was to validate the analysis done by the AI bot and to assess the benefits of using such a bot within daily operations. The results are reliable enough to consider having AI as a reliable assistant for repetitive operations and some more complex ones. In conclusion, this paper asserts that AI integration as a financial accountant assistant holds immense potential for transforming financial analysis, interpretation, and presentation processes, thereby enabling financial managers to fulfill their strategic role as business partners and value creators, thus transforming also the strategic role in further development for achieving sustainability and organizational resilience. It calls for continued research by peers specialists.